ANALISIS PROSES PENGAMBILAN KEPUTUSAN KONSUMEN ONLINE PADA SITUS BUKALAPAK DI KOTA PEKANBARU - Zulmi, Irawan; Sri, Restuti; Aida, Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims at finding out the analysis process of decision making of online consumer on Bukalapak site in Pekanbaru.The population of this research is the site of Bukalapak in Pekanbaru. The data collection was done by using a questionnaire with Non probability Sampling technique and the sample of the research is consisted of 165 people .The analysis of this study uses path analysis by the program of SPSS 20.The results show that: 1) Perceived Benefit Of Search affects theElectronic Word Of Mouthin the process of online decision making significantly on the site BukalaPak in Pekanbaru; 2) Perceived Benefit Of Search does not affect the Overall Deal Evaluationof the online decision-making process on BukalaPak website in Pekanbaru; 3) Perceived Benefit Of Search has significant effect on Overall Deal Evaluationthrough Electronic Word Of Mouth in the process of online decision making on BukalaPak site in Pekanbaru; 4) Overall Deal Evaluation has significant effecton Buying decision in the process of online decision making on BukalaPak site in Pekanbaru.Keywords: Perceived Benefit of Search, Electronic Word of Mouth, Overall Deal Evaluation, Buying Decision